2019
DOI: 10.2147/cia.s208098
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical performance of a bone-anchored annular closure device in older adults</p>

Abstract: Background: Lumbar discectomy is a common surgical procedure in middle-aged adults. However, outcomes of lumbar discectomy among older adults are unclear. Methods: Lumbar discectomy patients with an annular defect ≥6 mm width were randomized to receive additional implantation with a bone-anchored annular closure device (ACD, n=272) or no additional implantation (controls, n=278). Over 3 years follow-up, main outcomes were symptomatic reherniation, reoperation, and the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Controlled study (3) Barth, 2016 [22] 85-patient retrospective study Clinical outcomes with vs. without Barricaid over~2 years Trummer, 2013 [30] 75-patient retrospective study Facet degeneration with vs. without Barricaid over 1 year Vukas, 2013 [25] 102 [72] 554-patient RCT (NCT01283438) Clinical outcomes with Barricaid in older adults Bouma, 2019b [38] 554-patient RCT (NCT01283438) Analysis of failure-adjusted pain outcomes with vs. without Barricaid Bouma, 2019 c [39] 554-patient RCT (NCT01283438) Influence of patient blinding in an RCT with vs. without Barricaid Klassen, 2019 [70] 554-patient RCT (NCT01283438) Reoperation strategies with vs. without Barricaid Kursumovic, 2020 [40] 554-patient RCT (NCT01283438) Clinical implications of endplate changes with vs. without Barricaid over 4 years Health economics (6) Ament, 2019 [41] 554-patient RCT (NCT01283438) Direct & indirect costs of discectomy with vs. without Barricaid over 5 years Ament, 2019 [42] 554-patient RCT (NCT01283438) Direct costs of discectomy with vs. without Barricaid over 5 years Bostelmann, 2019 [43] 554-patient RCT (NCT01283438) Direct & indirect costs of discectomy with vs. without Barricaid over 2 years Klassen, 2018 [44] 554-patient RCT (NCT01283438) Costs of reoperation with vs. without Barricaid over 2 years Parker, 2013 [45] 76-patient comparative study Direct & indirect costs of discectomy with vs. without Barricaid over 1 year Thaci, 2019 [46] 554-patient RCT (NCT01283438) Direct costs of discectomy with vs. without Barricaid over 90 days Letters (7) Barth, 2018 [47] 554-patient RCT (NCT01283438) Letter re: endplate changes with vs. without Barricaid over 1 year Bouma, 2014 [48] 75-patient case series Letter re: clinical outcomes with Barricaid over 2 years Grasso, 2019 [49] 554-patient RCT (NCT01283438) Letter re: reoperation strategies with vs. without Barricaid Izci, 2014 [50] 75-patient case series Letter re: clinical outcomes with Barricaid over 2 years Klassen, 2017 [51] 554-patient RCT (NCT01283438) Erratum re: clinical outcomes with vs. without Barricaid over 90 days Lange, 2018 [52] Case report Letter re: case report of 1 patient who underwent Barricaid revision Shiban, 2018 [53] 554-patient RCT (NCT01283438) Letter re: endplate changes with vs. without Barricaid over 1 year Case reports (4) Gautschi, 2014 [54] Case report Case report of 1 patient successfully treated with...…”
Section: Symptomatic Reherniation and Reoperationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled study (3) Barth, 2016 [22] 85-patient retrospective study Clinical outcomes with vs. without Barricaid over~2 years Trummer, 2013 [30] 75-patient retrospective study Facet degeneration with vs. without Barricaid over 1 year Vukas, 2013 [25] 102 [72] 554-patient RCT (NCT01283438) Clinical outcomes with Barricaid in older adults Bouma, 2019b [38] 554-patient RCT (NCT01283438) Analysis of failure-adjusted pain outcomes with vs. without Barricaid Bouma, 2019 c [39] 554-patient RCT (NCT01283438) Influence of patient blinding in an RCT with vs. without Barricaid Klassen, 2019 [70] 554-patient RCT (NCT01283438) Reoperation strategies with vs. without Barricaid Kursumovic, 2020 [40] 554-patient RCT (NCT01283438) Clinical implications of endplate changes with vs. without Barricaid over 4 years Health economics (6) Ament, 2019 [41] 554-patient RCT (NCT01283438) Direct & indirect costs of discectomy with vs. without Barricaid over 5 years Ament, 2019 [42] 554-patient RCT (NCT01283438) Direct costs of discectomy with vs. without Barricaid over 5 years Bostelmann, 2019 [43] 554-patient RCT (NCT01283438) Direct & indirect costs of discectomy with vs. without Barricaid over 2 years Klassen, 2018 [44] 554-patient RCT (NCT01283438) Costs of reoperation with vs. without Barricaid over 2 years Parker, 2013 [45] 76-patient comparative study Direct & indirect costs of discectomy with vs. without Barricaid over 1 year Thaci, 2019 [46] 554-patient RCT (NCT01283438) Direct costs of discectomy with vs. without Barricaid over 90 days Letters (7) Barth, 2018 [47] 554-patient RCT (NCT01283438) Letter re: endplate changes with vs. without Barricaid over 1 year Bouma, 2014 [48] 75-patient case series Letter re: clinical outcomes with Barricaid over 2 years Grasso, 2019 [49] 554-patient RCT (NCT01283438) Letter re: reoperation strategies with vs. without Barricaid Izci, 2014 [50] 75-patient case series Letter re: clinical outcomes with Barricaid over 2 years Klassen, 2017 [51] 554-patient RCT (NCT01283438) Erratum re: clinical outcomes with vs. without Barricaid over 90 days Lange, 2018 [52] Case report Letter re: case report of 1 patient who underwent Barricaid revision Shiban, 2018 [53] 554-patient RCT (NCT01283438) Letter re: endplate changes with vs. without Barricaid over 1 year Case reports (4) Gautschi, 2014 [54] Case report Case report of 1 patient successfully treated with...…”
Section: Symptomatic Reherniation and Reoperationsmentioning
confidence: 99%
“…Investigation of sciatica treatments in older adults is an important pursuit since these individuals suffer from disability levels comparable to those with a history of chronic obstructive pulmonary disease, stroke, or myocardial infarction [71]. In order to address this question, a pooled analysis from multiple studies representing over 2,000 patient-years of follow-up identified several important clinical findings as it related to the Barricaid device and the aging adult [72]. First, older patients with large postsurgical annular defects had a high risk of symptomatic reherniation and reoperation that was comparable to younger patients.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Although the risk of osteoporosis is higher in older patients, older age is not a contraindication for treatment because older patients derive the same clinical benefit as younger patients with annular closure. 28 It should also be noted that the presence of the device does not interfere with standard reoperation strategies should one be indicated in the future. 29 Patients who successfully received the annular closure device and underwent reoperation were treated with similar reoperation techniques as patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies show worse outcomes, higher complication rate, and low satisfaction score following spinal surgery in the elderly, [4][5][6] other studies provide results of relatively high satisfaction rate with no added complication rate nor lesser outcomes. [7][8][9] Previous studies show a recurrence of back pain in about 25% of patients, during long-term follow-up, following LD. 10,11 Some provide the assumption that structural changes, after disc removal, are to blame.…”
Section: Introductionmentioning
confidence: 98%
“…While some studies show worse outcomes, higher complication rate, and low satisfaction score following spinal surgery in the elderly, 4 - 6 other studies provide results of relatively high satisfaction rate with no added complication rate nor lesser outcomes. 7 - 9 …”
Section: Introductionmentioning
confidence: 99%